2021
DOI: 10.3389/fonc.2021.773045
|View full text |Cite
|
Sign up to set email alerts
|

SENP2 Reduces Hepatocellular Carcinoma Stemness and Improves Sorafenib Sensitivity Through Inactivating the AKT/GSK3β/CTNNB1 Pathway

Abstract: BackgroundSmall ubiquitin-like modifier specific peptidase 2 (SENP2) suppresses the progression and chemoresistance of several cancers, while few studies report its role in hepatocellular carcinoma (HCC). This study aimed to evaluate the effect of SENP2 on stemness, sorafenib sensitivity, and downstream pathway in HCC, with validation of its molecular mechanisms by compensation experiment.MethodsSENP2 was regulated by plasmid transfection; meanwhile, in a compensation experiment, protein kinase B (AKT) was act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Finally, all cells were incubated with DMEM/F12 medium (Gibco, USA) supplemented with 20 ng/ml of EGF (Gibco, USA), 10 ng/ml of bFGF, and 10 μl/ml of B27 (Gibco, USA) for 10 days. The number of spheres (diameter > 50 µm) was counted under a microscope ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, all cells were incubated with DMEM/F12 medium (Gibco, USA) supplemented with 20 ng/ml of EGF (Gibco, USA), 10 ng/ml of bFGF, and 10 μl/ml of B27 (Gibco, USA) for 10 days. The number of spheres (diameter > 50 µm) was counted under a microscope ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it is essential to discover additional robust indicators for efficacy prediction and therapeutic target potential therapeutic targets. An increasing number of studies have addressed the importance of cancerous stemness and DNA methylation for drug sensitivity and resistance [ 22 , 30 , 31 ]. Beyond this, genome instability markers, including TMB, HRD, MSI, and MMR deficiency, were also reported to yield a profound impact on the immunotherapeutic response profiles [ 18 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly acknowledged that stemness is important for cancer metastasis and recurrence, contributing as well to drug resistance, resulting in poor patient prognosis. Overexpression of SENP2 has been shown to diminish HCC stemness and to sensitize cells to sorafenib [ 109 ]. HCC cell lines have lower SENP2 levels than normal human liver epithelial cell lines, while HCC stem cells had much lower levels than regular HCC cells.…”
Section: Sumo Proteases In Cancermentioning
confidence: 99%
“…HCC cell lines have lower SENP2 levels than normal human liver epithelial cell lines, while HCC stem cells had much lower levels than regular HCC cells. Mechanistically, SENP2 overexpression results in inhibition of the AKT/GSK3β/CTNNB1 pathway, which is linked to stemness suppression and drug sensitivity increase of HCC cells [ 109 ]. Meanwhile, a study with bladder cancer cells revealed that overexpression of SENP2 suppresses the TGFβ pathway and the ensuing EMT, preventing cell invasion.…”
Section: Sumo Proteases In Cancermentioning
confidence: 99%